Association between a History of herpes zoster and the risk of Sjögren's syndrome: a nationwide, population-based, case–control study. Issue 10 (14th October 2022) - Huang, Pei Ju; Lin, Shih-Ping; Wu, Chun-Yi; Liu, Yen-Tze; Chen, Hsin-Hua
Abstract : Objective: Viral infection is an exogenous factor for Sjögren's syndrome (SS). The relationship between herpes zoster infection and the ensuring risk of SS has remained unclear. This study investigated the association between a history of herpes zoster infection and the risk of SS through a nationwide population-based case–control study. Design: Retrospective case–control study. Setting: General population of Taiwan. Data source: 2003–2013 National Health Insurance Research Database of Taiwan. Participants: We identified all patients with newly diagnosed SS between 1 January 2007 and 31 December 2012 without a history of rheumatoid arthritis or systemic lupus erythematosus as the SS group. Controls: We randomly selected patients without SS between 1 January 2003 and 31 December 2012 and matched 1:5 with controls based on index year, age and sex. Main outcome measure: Conditional logistic regression analysis to examine the association between a history of herpes zoster and the risk of SS. Results: The study included 5751 patients with SS and 28 755 matched controls. The risk of SS was significantly associated with a history of herpes zoster (model A (adjusted for Charlson Comorbidity Index (CCI) (excluding connective tissue disease, CTD)): OR 1.89; 95% CI 1.71 to 2.08; model B (adjusted for comorbidities used to calculate CCI (excluding CTD)): OR 1.90; 95% CI 1.72 to 2.10), in particular if the interval from the last visit for herpes zoster infection to the index date was <3 months (model A: OR 3.09; 95% CI 2.20 to 4.34; model B: OR 3.13; 95% CI 2.20 to 4.45). Such associations remained robust using various definitions of herpes zoster. Conclusion: This nationwide, population-based, case–control study revealed a significant association between a history of herpes zoster and the risk of SS.